DRIVING FORCE OF E-LOYALTY IN ONLINE BANKING SECTOR IN THE CONTEXT OF MALAYSIA - Chowdhury, Iftekhar; Othman, Abdullah; Bo, Yang; Huey, Lim (PEOPLE: International Journal of Social Sciences, 2017)
The development of customer loyalty in online banking has become a basic issue because of the positive and constructive influence on banks' long haul productivity. With increasing Internet access, the competition is only one tick away. Customer loyalty in online banking sector appears to be essential for electronic banks both in a competitive and additionally an economic sense. Hence, there is a need to understand how customer loyalty in the online banking sector is created. Previous studies found that e-service quality, e-satisfaction, and e-trust have direct or indirect effects on the creation of e-loyalty. However, previous studies just demonstrated a piece of relationships between these variables and their effects on e-loyalty. A hole can be discovered that there is not a comprehensive view on all of the effects that service quality, customer satisfaction, and customer trust have on customer loyalty in the context of online banking. Therefore, the present research tried to provide a comprehensive model to fill the crevice of previous literature and demonstrate the relationship of e-service quality, e-satisfaction, and e-trust with e-loyalty in the online banking sector. The target sample in this investigation was experienced Internet banking users. Based on the investigation, it is discovered that e-satisfaction and e-trust assume the real role to construct e-loyalty in the online banking sector. However, e-service quality is not a predictor of customer e-loyalty towards Internet banking websites. It means that customers tend not to be steadfast even. However, the online banking service providers provide great services. The investigation impediments, suggestions, alongside directions for further research are discussed.